Research on Self-compensating Oil Sleeve for Hydraulic Chuck. Issue 1 (February 2021) - Yang, Jiangbo; Wang, Song; Xu, Pengbo; Chen, Xiang; Chen, Fenglei
Abstract: Based on the oil supply principle of hydraulic chuck, analysis of the structural characteristics and failure reasons of the oil distribution sleeve showed that the main reason for the increase of the leakage of the oil sleeve is the increase of the value of the seal gap caused by the increase of the temperature and pressure of the hydraulic oil. The self-compensating oil sleeve for the rotary oil distribution of hydraulic chuck is designed by theoretical calculation, and the deformation of the self-compensating oil distribution sleeve and the common oil distribution sleeve are compared and analyzed by finite element software, and the sealing performance of the two kinds of oil sleeve is compared and analyzed by test. The results show that the sealing gap of the self-compensating oil sleeve has dynamic stability compared with that of the ordinary oil sleeve, and the leakage of the self-compensating oil sleeve is stable under the working condition, which can provide reference for the design innovation of the rotary oil distribution sleeve for the chuck of the full hydraulic drilling machine.